The Effect of Health Counseling on Maternal Knowledge Regarding Stunting: Pre-experimental Study - Rahmawati, Nisa; Sukmawati, Ima; Rahayu, Yuyun (Genius Journal, 2024)
Introduction: Education plays a crucial role in empowering mothers with the knowledge necessary to optimize the care and development of their toddlers. Understanding the impact of health education on maternal knowledge is essential to improve health outcomes for young children and support effective parenting practices. Objective: This study aims to analyze the effect of health education on the knowledge levels of mothers with toddlers. Method: This study employed a pre-experimental design using a one-group pre-test and post-test approach. The population consisted of mothers with children under five years old (toddlers), with a sample of 33 participants selected through accidental sampling. The study was conducted in Wado, Sumedang Regency, from March 20 to April 20, 2024. Data analysis was performed using the Wilcoxon signed-rank test to evaluate the effect of health education on maternal knowledge. Result: The results of this study indicated an increase in the knowledge of mothers with toddlers, from a moderate category (48.5%) to a good category (90.9%). The P-value obtained was 0.000 (˂ 0.05), indicating a significant effect of health education on stunting prevention on maternal knowledge. Conclusion: This study concludes that health education significantly enhances maternal knowledge about stunting prevention, with a shift from moderate to good understanding. These findings highlight the effectiveness of health education as a key intervention in improving maternal awareness. Integrating structured health education programs into community healthcare strategies is essential to reducing stunting prevalence and promoting better child health outcomes.